2017
DOI: 10.3389/fonc.2016.00269
|View full text |Cite
|
Sign up to set email alerts
|

GATA1 Activity Governed by Configurations of cis-Acting Elements

Abstract: The transcription factor GATA1 regulates the expression of essential erythroid and megakaryocytic differentiation genes through binding to the DNA consensus sequence WGATAR. The GATA1 protein has four functional domains, including two centrally located zinc-finger domains and two transactivation domains at the N- and C-termini. These functional domains play characteristic roles in the elaborate regulation of diversified GATA1 target genes, each of which exhibits a unique expression profile. Three types of GATA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 84 publications
(92 reference statements)
0
12
0
Order By: Relevance
“…In erythroid differentiation, GATA1 is an essential transcription factor involved in a considerable number of target genes that regulate the proliferation, differentiation, and survival of hematopoietic progenitors. 24 Therefore, lncRNA regulated by GATA1 is more likely to play a role in erythropoiesis. To screen for potential GATA1-regulated lncRNAs, we first analyzed the ChIP-seq data from K562 erythroid cells in the ENCODE database and identified 107 lncRNAs with GATA1 binding sites within 2 kb of their genes.…”
Section: Resultsmentioning
confidence: 99%
“…In erythroid differentiation, GATA1 is an essential transcription factor involved in a considerable number of target genes that regulate the proliferation, differentiation, and survival of hematopoietic progenitors. 24 Therefore, lncRNA regulated by GATA1 is more likely to play a role in erythropoiesis. To screen for potential GATA1-regulated lncRNAs, we first analyzed the ChIP-seq data from K562 erythroid cells in the ENCODE database and identified 107 lncRNAs with GATA1 binding sites within 2 kb of their genes.…”
Section: Resultsmentioning
confidence: 99%
“…Hematopoietic homeostasis is maintained by a refined equilibrium between selfrenewal, proliferation, differentiation and survival of hematopoietic stem cells and their progeny with each process being supported by the balanced expression of several specific genes, regulated by different transcription factors. In this context, the GATA-1 factor plays a key role in regulating the expression of a large set of hematopoietic-related genes [32,61]. Therefore, not surprisingly, its dysregulated expression is emerging as a key factor in malignant hematopoiesis [32,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] Initially, it was shown that GATA1 binds to a WGATAR sequence motif. However, genome-wide studies of GATA1 chromatin occupancy have revised this original sequence motif and have highlighted the presence of single and dual (tandem or palindromic) GATA1 motifs and composite elements containing a sequence motif for collaborative transcription factors (for a review, see 17 ). GATA1 functions as either an activator or a repressor, depending on the gene context.…”
Section: Gata1mentioning
confidence: 99%